Oxygen–steam gasification of karanja press seed cake: Fixed bed experiments, ASPEN Plus process model development and benchmarking with saw dust, rice husk and sunflower husk. Issue 2 (April 2018) - Dhanavath, Kotaiah Naik; Shah, Kalpit; Bhargava, Suresh K.; Bankupalli, Satyavathi; Parthasarathy, Rajarathinam
Graphical abstract: Highlights: Investigating the oxygen–steam gasification of Karanja PSC using experimental and modeling activities. The detailed model for the entire system is built with Aspen Plus. Sensitivity analyses are done to detect the effects of key operating parameters. Maximum H2 and CO molar yields are achieved at higher temperature and low oxygen content. The simulations with present model are in better agreement with experimental data. Abstract: This article aims at investigating the oxygen–steam gasification of Karanja press seed cake using experimental and modeling studies and compare the results of these studies with those for other feedstocks such as rice husk, sawdust, and sunflower husk. The experimental work was conducted in a fixed bed reactor and the process simulation model was created in ASPEN Plus. Finally, validation and benchmarking exercise were conducted by validating the ASPEN Plus model using experimental results. A general agreement was found between the experimental results and ASPEN Plus process model results with a maximum variation of ±4%. Furthermore, sensitivity analyses were carried out to understand the effects of parameters such as gasification temperature, ER (equivalence ratio), and SBR (steam to biomass ratio) on synthesis gas composition, LHV (lower heating value) and CGE (cold gas efficiency). The optimal values of ER and SBR in this study were found to be 0.23 and 0.3, respectively. The CGE was found to increase with an increase in the temperature. Values of CGE and LHV were found to be as high as 95% and ∼12 MJ/Nm 3, respectively at 1000 °C for all feedstocks. The optimum SBR value was found to vary from 0.3 to 0.7 for H2 /CO variation in the range of ∼0.83–1.0.